To find the interval where \((f - g)(x) < 0\), we first need to express \((f - g)(x)\) explicitly.
Given:
- \(f(x) = x - 3\)
- \(g(x) = -0.5x\)
Now, the expression for \((f - g)(x)\) is:
\[ (f - g)(x) = f(x) - g(x) = (x - 3) - (-0.5x) \]
This simplifies to:
\[ (f - g)(x) = x - 3 + 0.5x = 1.5x - 3 \]
Next, we need to find when this expression is negative:
\[ 1.5x - 3 < 0 \]
Solving for \(x\):
\[ 1.5x < 3 \]
\[ x < \frac{3}{1.5} = 2 \]
Thus, \((f - g)(x) < 0\) for \(x < 2\).
Now we consider the intervals given:
- \((-\infty, -1)\)
- \((-\infty, 2)\)
- \((0, 3)\)
- \((2, \infty)\)
The interval where \((f - g)(x)\) is negative is:
\[ \text{The correct answer is } (-\infty, 2). \]